(untitled) (Research, Society and Development, 2022)
This work presents a brief explanation about the exaggerated use of the figure of the Metropolitan Region in Brazil. This use is only figurative, for in fact few should be considered as such. Including the possibility of reviewing the formalization as a Metropolitan Region. The Metropolis Statute itself brings options such as urban agglomerations and micro-regions as forms of management to the detriment of the Metropolitan Region. This fact leaves gaps to be filled, such as the possibility of micro-regions becoming a management scale. As many contributions to the Metropolis Statute have not been clarified, the intention is to investigate whether the current microregions correspond to the proposal of the Metropolis Statute. For the elaboration of the present work, bibliographic research was carried out and secondary data collection was carried out on the regions in Spain and on the microregions in the state of Paraná-Brazil. Shared management can fill the gaps in territorial policy in Paraná and Brazil, provided that well-structured, prioritizing the demands of each municipality or each association of municipalities.